Realising the Potential : Assessing Professional Learning through the Integration of ePortfolios in Australian Business Education : Final Report. - Watty, Kim; Kavanagh, Marie; McGuigan, Nick; Leitch, Shona; Holt, Dale; Ngo, Leanne; McKay, Jade; Davies, Jill; McCormick, Terry (Office for Learning and Teaching, 2016)
This project enabled academic leadership of Australian Business and Management education programs to design into the curriculum, and best use, ePortfolios and associated technologies in assessing students' learning of highly valued professionally-based capabilities. The project investigated and supported the best ways of broadly and deeply embedding ePortfolios across entire undergraduate business and management education curricula. ePortfolios for enabling and assessing student learning is seen as a key means for integrating student learning across the curriculum and, therefore, creating a holistic learning experience. The project worked with Program Leaders across the sector through liaison with the Australian Business Deans Council (ABDC), Teaching and Learning Network to both draw in better practices and disseminate project findings as the project progresses through its key phases. These planned actions will lead to the progressive development of a Business Education ePortfolio Professional Learning Capabilities Assessment Framework.